KOMUNIKASI DUA ARAH MODUL PENGENDALI MOTOR ALAT TRIAXIAL DIGITAL - Saputra, Hendri Maja; Saputra, Ivan Heru; A.H.B.Baskoro, Catur Hilman (AUSTENIT, 2021)
This study aims to apply two-way communication module for motor controller on digital triaxial test equipment. In the triaxial digital test equipment, the speed and direction of up / down motors in the previous version is still manually controlled by pressing the push button on the control panel. In this research is done digitalize all process at control panel, so that all activity of control tool can be done in front of computer. The communication between the computer and the digital triaxial test device uses a serial communication directly connected to the motor controller module, where the computer sends only characters that will be processed by the microcontroller. The microcontroller translates characters sent, processed, and gives commands to be forwarded to displays and motors. Testing is done directly using Gerlink Triaxial application on computer. Based on some test results obtained that the character sent by the computer can move and change the speed of the motor, and rearrange the loadcell readings on triaxial test equipment. The data rate sent each character is 1.04 milliseconds each.